THE INFLUENCE OF COOPERATIVE LEARNING MODEL TYPE TEAMS GAMES TOURNAMENT ON THE STUDENT LEARNING OUTCOMES OF 7th GRADER ABOUT CLASSIFICATION OF LIVING THINGS - ANGGRAINI, RINI; Oktavia, Rani (Department of Science Education, 2025)
The research aims to determine the effect of using the Teams Games Tournament type of cooperative learning model on the learning outcomes of 7th grader about classification of living things. The type of research used is Quasi Experiment with a research design that is Posttest Only Control Group Design. The population of this research is 7th grader of SMP Negeri 2 Kota Solok. The sampling technique used is purposive sampling technique. The sample used is class VII-9 as the control class using the conventional model while class VII-10 is the experimental class using the Teams Games Tournament cooperative learning model. The instrument used was a test in the form of multiple choice questions totaling 14 questions. The results of the calculation of the hypothesis test using the t-test with a significant level ? = 0.05 indicate the value of zcount>ztable, namely z0=6,4 and zt=1,96. Thus the research H0 is rejected and Ha is accepted where there is an influence of the Teams Games Tournament type cooperative learning model on the learning outcomes of 7th grader in material classification of living things at SMP Negeri 2 Kota Solok.